Implementasi Program Budaya Sekolah 5S (Senyum, Salam, Sapa, Sopan, Santun) dalam Menanamkan Religiusitas Siswa (Studi Multisitus) - Widya Khairunnisah; Salminawati Salminawati; Zaini Dahlan (Ideguru: Jurnal Karya Ilmiah Guru, 2024)
This research aims to determine the planning, implementation and evaluation and implementation of the 5S (Smile, Greet, Greet, Polite, Polite) school culture program towards cultivating the character of student religiosity at Madrasah Ibtidaiyah Negeri (MIN) 6 Langkat and Madrasah Ibtidaiyah Negeri (MIN) 6 Medan. This research is included in the type of qualitative descriptive research with the type of multisite study. Through a multisite study approach, this research examines the impact of the 5S program on the formation of religious values. Data mining methods in this research include: observation, interviews, and documentation studies to gain an in-depth understanding of the effectiveness of this program. It is hoped that the research results can provide useful insights in improving students' religious aspects through implementing 5S school culture. The results of this research show that 1) The 5S school culture program implemented at MIN 6 Langkat and MIN 6 Medan is planned based on the vision, mission and goals of the Institution; 2) The implementation of the 5S school culture program at MIN 6 Langkat and MIN 6 Medan aims to shape students' religious character, carried out by making congregational prayers a habit, a clean environment, infaq/almsgiving, and a culture of Al-Qur'an literacy being part of daily activities; 3) Continuous evaluation is carried out to evaluate the effectiveness of the program and develop improvements to increase its impact in shaping student character and spirituality.